The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/pits.22709
|View full text |Cite
|
Sign up to set email alerts
|

Greek teachers' resilience levels during the COVID‐19 pandemic lockdown and its association with attitudes towards emergency remote teaching and perceived stress

Abstract: The mandatory closure of schools due to the Covid‐19 pandemic affected the mental health, and, by extension, the personal and professional life of teachers. This study explored their level of resilience during the pandemic and its association with attitudes towards emergency remote teaching and perceived stress. Data were collected through the administration of three self‐report instruments: (a) the “Teachers' Professional Attitudes and Behaviors Scale”, (b) the “Teachers' Resilience Scale”, and (c) the “Perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
(56 reference statements)
2
10
0
Order By: Relevance
“…The correlations between the level of teacher resilience measured with the CD-RISC-10 with the beliefs, knowledge and resources that teachers possess in resilience (C-DPR) confirm the relationship between the resilience measure and the competencies of teachers as resilient professionals. This is in line with studies that highlight that resilience is not a fixed trait or attribute, but a state variable that can be developed so it is considered important that teachers receive training in resilience [ 19 , 20 , 47 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The correlations between the level of teacher resilience measured with the CD-RISC-10 with the beliefs, knowledge and resources that teachers possess in resilience (C-DPR) confirm the relationship between the resilience measure and the competencies of teachers as resilient professionals. This is in line with studies that highlight that resilience is not a fixed trait or attribute, but a state variable that can be developed so it is considered important that teachers receive training in resilience [ 19 , 20 , 47 ].…”
Section: Discussionsupporting
confidence: 85%
“…Despite not finding significant differences, with respect to the sex variable, a higher mean resilience was obtained in men. In the literature, there are some studies that obtained a higher level of resilience in men [ 59 ] and other studies in women [ 47 ], so we can intuit that sex does not have a direct relationship with the development of resilience, although further research is needed.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies have found that Greek teachers have demonstrated moderate to high levels of resilience (e.g., Botou et al, 2017;Daniilidou, 2018Daniilidou, , 2023Hatzichristou et al, 2017;Papazis et al, 2022;Stavraki & Karagianni, 2020).…”
Section: Resilience Of Greek and Polish Teachers And Sociodemographic...mentioning
confidence: 99%